Plan de gestión proyecto de transmisión Peñas Blancas - Garita - Camacho-Rodríguez, Juan Carlos (Instituto Tecnológico de Costa Rica, 2005)
The Instituto Costarricense de Electricidad is the sole governing entity in charged of the development of the national’s electric sector and in consequence, plays the same role for the national network transmission of high and low tension which belongs to the SIN (Sistema Interconectado Nacional). It develops and executes electric transmission projects by means of the Unidad Estratégica de Negocio Proyectos y Servicios Asociados, which is the unit in charged of the design and execution of projects related to electric generation and transmission. The following investigation is focused on elaborating a plan for the Proyecto Transmisión Peñas Blancas – Garita and the five works that constitute it (transmission lines and substations). In addition, aspects such as organization, involved entities, financing, system controls, possible risks, administration and execution, among other elements, are identified in order to satisfy the customer’s needs (Unidad Estratégica de Negocio Transporte de Energía) responsible for the electric transportation and providing maintenance to the country’s infrastructure. Finally, it is intended to establish a course of action in the executory of the works mentioned above, which then can provide more control over the operation and consequently obtain complete customer satisfactory.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2005.
Keywords: Administración de riesgos; Herramientas de control; Conducción eléctrica; Interconexión; Marco de acción